Effect of supplemental protein:ratio on the intake, digestibility, fill, and turnover of dormant bluestem range-grasses - DelCurto, T.; Cochran, R.C.; Jacques, K.A.; Harmon, D.L.; Towne, G.; Avery, T.B.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding a low crude protein (12%) supplement depressed dormant bluestem range-grass fiber digestibility, whereas moderate (27%) and high (41 %) protein supplementation maintained forage digestibility and encouraged intake. Increased intake for moderate and high protein groups appeared to be associated with increased rumen dry matter and indigestible fiber fill.
Keywords: Beef; Protein:Energy ratio; Intake; Digestibility; Fill; Bluestem